2023
DOI: 10.3390/ijms24043884
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Reveals the Effect of Short-Term Freezing on the Signal Transduction and Metabolism of Grapevine

Abstract: Low temperature is an important factor limiting plant growth. Most cultivars of Vitis vinifera L. are sensitive to low temperatures and are at risk of freezing injury or even plant death during winter. In this study, we analyzed the transcriptome of branches of dormant cv. Cabernet Sauvignon exposed to several low-temperature conditions to identify differentially expressed genes and determine their function based on Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG)enrichment analyses. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Climate predictions and simulations indicate that climate change will pose a signicant challenge for wine production in the future. A comprehensive understanding of the characteristics Grapes Reduce ability to synthesize long-chain unsaturated fatty acids 52 of frost events is essential for early detection, allowing for strategic crop management decisions, such as determining whether the crop should be cut for hay or harvested for grain. However, harvesting grapes is not the only measure a producer can resort to, and even this decision may affect the quality of the produced grapes, considering the possibility that the grapes are still not ready to be harvested.…”
Section: Viniculture Anti-frost Controlmentioning
confidence: 99%
“…Climate predictions and simulations indicate that climate change will pose a signicant challenge for wine production in the future. A comprehensive understanding of the characteristics Grapes Reduce ability to synthesize long-chain unsaturated fatty acids 52 of frost events is essential for early detection, allowing for strategic crop management decisions, such as determining whether the crop should be cut for hay or harvested for grain. However, harvesting grapes is not the only measure a producer can resort to, and even this decision may affect the quality of the produced grapes, considering the possibility that the grapes are still not ready to be harvested.…”
Section: Viniculture Anti-frost Controlmentioning
confidence: 99%
“…Since the availability of the grapevine genome (initially in 2007 and later re-sequenced in 2019), omics-based studies have been extensively used to study polyploidy and heterozygosity in grapevines ( The French–Italian Public Consortium for Grapevine Genome Characterization, 2007 ; Liang et al., 2019 ). For example, in a recent study conducted by ( Han et al., 2023 ), the authors used reference genome-based RNA-seq data analysis to identify the probable pathways involved in the freezing response in grapevines. Likewise, a few studies were conducted on grapevine breeding using various omics technologies ( Wang et al., 2021 ; Savoi et al., 2022 ).…”
Section: Choosing the Best Individual: Omics Based Genomic Selection ...mentioning
confidence: 99%
“…However, the plant resistance to very cold and freezing temperatures has not been extensively studied yet despite recent advances in sequencing and molecular biotechnology ( Ren et al., 2023 ). Also, not much is known about the impact of different temperatures on the gene expression patterns of Vitis vinifera ( Han et al., 2023 ). Experiments done under various cold stress conditions showed that the freeze-shock damages plant leaves more than long-term freezing ( Londo et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%